Analisis Peningkatan Ekonomi Nelayan di Kecamatan Siberut Tengah - S, Nadya Savitri; Ramadhan, Risky (Al-DYAS, 2025)
Siberut Tengah sub-district has high potential in the fisheries sector, this is supported by the location of the area in an archipelagic area surrounded by sea. Due to the existence of supporting resources, many people in Central Siberia work as fishermen, either as full-time fishermen or on the side. Therefore, this research aims to determine the existing conditions of capture fisheries and to determine the economy of fishermen in Cyberut Tengah sub-district, guided by 7 welfare indicators according to BPS 2014. The method used in this research is quantitative descriptive. The results of the research show: 1. Based on the results of interviews with fishermen, there are 6 fishing locations and 5 fish marketing locations. 2. The RZWP3K zone is divided into 4, namely: tourism zone (0.58 km2), port zone (0.096 km2), aquaculture zone (5.66 km2) and capture fisheries zone (90.66 km2). 3. Of the 95 fishermen, 42 are prosperous and 53 are not prosperous.